Association of Rheumatoid Arthritis Serology Markers with Echocardiographic Global Longitudinal Strain: A Single-Center Cross-Sectional Study in Iran - Delkash, Parisa; Omidi, Fatemeh (Novelty in Biomedicine, 2024)
Background: Rheumatoid arthritis (RA) is associated with increased cardiovascular morbidity and mortality, attributed in part to myocardial dysfunction. Global longitudinal strain (GLS) measured by speckle-tracking echocardiography is a sensitive marker of myocardial function. This study aimed to investigate the association between RA serology markers, including rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) antibodies, and GLS in RA patients. Materials and Methods: This one-year cross-sectional study was conducted at Imam Hossein Hospital in Tehran, Iran, focusing on patients diagnosed with RA. Rheumatoid arthritis serology markers, including RF and anti-CCP antibodies, were assessed. GLS was measured using speckle-tracking echocardiography. The association between RA serology markers and GLS categories was analyzed using chi-square tests with IBM SPSS Statistics version 26. Results: A total of 71 patients were included in the study, with a mean age of 52.31 years. Among the RA patients, 28 individuals (71.8%) with negative RA serology exhibited abnormal GLS values, while 11 (28.2%) had normal GLS values. Conversely, all 21 (100%) RA patients with positive serology showed abnormal GLS values. Statistical analysis revealed no significant association between RA serology markers and GLS category (χ2 = 0.313, P>0.05). Conclusion: In this study, RA serology markers, including RF and anti-CCP antibodies, were not significantly associated with GLS abnormalities in RA patients. Further research is needed to elucidate other factors contributing to myocardial dysfunction in RA.